1983
DOI: 10.1017/s0022112083001378
|View full text |Cite
|
Sign up to set email alerts
|

Experiments on the turbulence statistics and the structure of a reciprocating oscillatory flow

Abstract: A reciprocating oscillatory turbulent flow in a rectangular duct is investigated experimentally by making use of a laser-Doppler velocimeter, hot-wire anemometers as well as electronic digital sampling and processing equipments.The profiles of the mean velocity, the turbulence intensities, the Reynolds stress and the turbulent-energy production rate are compared for the accelerating and decelerating phases.The characteristics of such a flow are quite different from wall turbulence which is steady in the mean. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

34
178
3

Year Published

1998
1998
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 240 publications
(215 citation statements)
references
References 17 publications
34
178
3
Order By: Relevance
“…Here, explosive turbulent near-wall bursts appear during the deceleration phase, while the flow relaminarizes during acceleration. 6 For higher Re S , the flow becomes turbulent in earlier phases and remains turbulent for longer periods. A study by Jensen et al 2 showed that fully developed turbu-lence is already present during most of the oscillation cycle at Re S ϳ 1800, while the flow remains turbulent during the complete cycle for Re S Ͼ 3500.…”
Section: Introductionmentioning
confidence: 97%
“…Here, explosive turbulent near-wall bursts appear during the deceleration phase, while the flow relaminarizes during acceleration. 6 For higher Re S , the flow becomes turbulent in earlier phases and remains turbulent for longer periods. A study by Jensen et al 2 showed that fully developed turbu-lence is already present during most of the oscillation cycle at Re S ϳ 1800, while the flow remains turbulent during the complete cycle for Re S Ͼ 3500.…”
Section: Introductionmentioning
confidence: 97%
“…The turbulence near a hydraulic structure has been the subject of theoretical and experimental research for the past few decades due to sediment transport (Hino et al 1983;Nagata et al 2005;Raupach et al 1991;Raupach and Thom 1981;Speziale 1990). Sediment transport is highly intermittent and it was hypothesized that this was due to an intermittence of the turbulent intensities caused by coherent structures of the turbulent flow field (Grass 1971;Raupach et al 1996;Rhoads and Massey 2012).…”
Section: Parameters and Methodsmentioning
confidence: 99%
“…(7) (8) (degree) (9) Hereafter, the values of a, as function of a from three approximation of phase difference are plotted in Fig. 8.…”
Section: Experimental Methodsmentioning
confidence: 99%